26. Histopathology view of thymus in broiler chickhen Infected by Escherichia coli And Given Kemangi Leaves (Ocimum basilicum ) Extract - Doly Ihsan Siregar; Hamdani Budiman; Dwina Aliza; Ummu Balqis; Nuzul Asmilia; Ismail Ismail (Jurnal Medika Veterinaria, 2019)
The aim of this study was to determined effect of kemangi leaves extract on level of doses to changes of microcsopic structure of broiler thymus which infected by Escherichia coli (E. coli). This study used 15 DOC that raised for 34 days. Broiler divided into 5 treatment group with 3 repetition. Negative control (A0) given standard feed, positive control (A1) given standard feed and infected with E.coli. Group A2, A3, and A4 given standard feed and infected with E. coli, added with kemangi leaves extract in concentration of 2,5%, 3,5%, and 4,5%. E. coli infected through intra peritonium as much of 0,25 ml on 15th days. Kemangi leaves extract were given from 7th days to 34th days. Observation on A1 showed many empty room. A2 and A3 showed a bit repairement on thymus microscopic structure. In A4 thymus showed approaching normal appearance as in A0. In conclusion, kemangi leaves extract capable to repair microscopic structure of broiler thymus which infected with E. coli. Kemangi leaves administration at 4,5% dose had a better effectivity rather than dose of 2,5% and 3,5%.